Real-Word Effectiveness of Global COVID-19 Vaccines Against SARS-CoV-2 Variants: A Systematic Review and Meta-Analysis - Wang, Kai; Wang, Lin; Li, Mingzhe; Xie, Bing; He, Lu; Wang, Meiyu; Zhang, Rumin; Hou, Nianzong; Zhang, Yi; Jia, Fusen (Frontiers in Medicine, 2022)
Abstract Background: Nowadays, promoted vaccinations against SARS-CoV-2 are being carried out globally, however, the occurrence of numerous COVID-19 variants has dampened the wish for a rapid mitigation of the COVID-19 pandemic by effectively mass vaccinations. The real-word effectiveness of the current vaccines against COVID-19 variants hasn’t been assessed by published reviews. Therefore, our study evaluated the overall effectiveness of vaccines for COVID-19 and the differences between vaccines and variants types. Methods: PubMed, Embase, Cochrane Library, medRxiv, bioRxiv and arXiv were retrieved to screen the eligible studies. The Egger test and the Newcastle–Ottawa scale were applied to estimate the publication bias and the quality of the literatures, respectively. The pooled incident rates of different variants after vaccination were estimated by single-arm analysis. Meanwhile, the pooled efficacies of various vaccines against variants was evaluated through the odds ratio (OR) and vaccine effectiveness (VE) by two-arm analysis. Results: 3306 studies were identified initially and 16 articles were included. We found that the overall incidence of variants post first /second vaccine were 0.06 and 0.02, respectively; the VE of incidence of variants post first vaccine between the vaccine and the placebo or unvaccinated population was 0.38 and post second vaccine was 0.80, respectively. The sub-single-arm analysis showed low prevalence rate of the COVID-19 variants after specific vaccination with the pooled incidence below 0.10 in most subgroups. Meanwhile, the sub-two-arm analysis indicated that most current vaccines had good or moderate preventive effect on certain variants considering that the VE in these subgroups were between 66% and 86%, which were broadly in line with the results of the sub- single-arm analyse. Conclusion: Our meta-analysis shows that the current vaccines that are used globally could prevent the covid-19 infection and restrict the spread of variants to a great extend. We would also support maximising vaccine uptake with 2 doses as the effectiveness of which were more marked comparing with 1 dose. Although the mRNA vaccine was the most effective against variants by our study, specific vaccine should be taken into account based on the local dominant prevalence of variants.